Biostimulant Action of Protein Hydrolysates: Unraveling Their Effects on Plant Physiology and Microbiome - Colla, Giuseppe; Hoagland, Lori; Ruzzi, Maurizio; Cardarelli, Mariateresa; Bonini, Paolo; Canaguier, Renaud; Rouphael, Youssef (Frontiers in Plant Science, 2017)
Plant-derived protein hydrolysates (PHs) have gained prominence as plant biostimulants because of their potential to increase the germination, productivity and quality of a wide range of horticultural and agronomic crops. Application of PHs can also alleviate the negative effects of abiotic plant stress due to salinity, drought and heavy metals. Recent studies aimed at uncovering the mechanisms regulating these beneficial effects indicate that PHs could be directly affecting plants by stimulating carbon and nitrogen metabolism, and interfering with hormonal activity. Indirect effects could also play a role as PHs could enhance nutrient availability in plant growth substrates, and increase nutrient uptake and nutrient-use efficiency in plants. Moreover, the beneficial effects of PHs also could be due to the stimulation of plant microbiomes. Plants are colonized by an abundant and diverse assortment of microbial taxa that can help plants acquire nutrients and water and withstand biotic and abiotic stress. The substrates provided by PHs, such as amino acids, could provide an ideal food source for these plant-associated microbes. Indeed, recent studies have provided evidence that plant microbiomes are modified by the application of PHs, supporting the hypothesis that PHs might be acting, at least in part, via changes in the composition and activity of these microbial communities. Application of PHs has great potential to meet the twin challenges of a feeding a growing population while minimizing agriculture’s impact on human health and the environment. However, to fully realize the potential of PHs, further studies are required to shed light on the mechanisms conferring the beneficial effects of these products, as well as identify product formulations and application methods that optimize benefits under a range of agro-ecological conditions.